A Credible Routing Based on a Novel Trust Mechanism in Ad Hoc Networks. (22nd April 2013) - Feng, Renjian; Che, Shenyun; Wang, Xiao; Yu, Ning
Abstract : Many existing routing protocols in Mobile Ad hoc Networks (MANETs) focus on finding paths in dynamic networks without considering security. In this paper, we propose a trust model which evaluates neighbours' direct trust by factors of encounter time, mobility, and successful cooperation frequency. The revised D-S evidence theory is used to combine multiple recommended pieces of evidence and obtain the recommended trust value. Then based on the novel trust mechanism, we propose a trusted routing protocol named TDS-AODV protocol by extending the AODV protocol. In this protocol, a node makes a routing decision according to the trust values of its neighbour nodes. Finally, two routes are built: the main route with highest route trust value in the candidate routes and a backup route. Simulation results reveal that TDS-AODV can eliminate malicious nodes effectively when building the route; furthermore, it also achieves better performance than TAODV and AODV in terms of throughput, packet delivery ratio, and average end to end delay.